The Effectiveness of Plasmapheresis Compared to Intravenous Immunoglobulin in Guillain-Barre Syndrome Patients - Mustika, Alyssa Putri; Hakim, Manfaluthy; Sari, Waode Satriana; Octaviana, Fitri; Budikayanti, Astri; Safri, Ahmad Yanuar; Wiratman, Winnugroho; Indrawati, Luh Ari; Fadli, Nurul; Harsono, Adrian Ridski; Savitri, Irma (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2024)
Introduction : Guillain-Barré syndrome (GBS) is the second most common cause of acute and subacute general paralysis. The management is symptom-adjusting, but plasmapheresis (plasma exchange/PE) and intravenous immunoglobulin immunotherapy (IVIG) can be administered to accelerate the return of neurological function. This study aim to determine PE's effectiveness compared to IVIG in GBS patients and the side effects or complications that may arise. Method : The literature study is carried out on four databases. Selection is carried out using inclusion and exclusion criteria. The articles were screened and extracted independently by two investigators. Results : The literature study obtained three systematic review studies. In the first study, shows the outcomes in the form of improved Hughes Score (OR 1.9; 95% CI 1.11-3.28) and mortality (OR 0.8; 95% CI 0.31-2.29) against IVIG. The second study, outcomes shown in the form of improved disability scores (WMD -0.02, p: 0.83), and secondary outcomes such as mortality or relapse (p >0.05, respectively). The third study showed that IVIG had higher efficacy (OR 1.6, p: 0.067, 95% CI 0.972-2.587), shorter duration of hospitalization, 38 days, compared to 49-day PE therapy (SMD -3.389, 95% CI -11.601-4.824; p: 0.419), however, had higher side effect (OR 0.8, p: 0.430, 95% CI 0.389-1.495). Conclusion : PE efficacy is generally lower than IVIG, as indicated by disability scores/motor ability scores in various studies, as well as the duration of hospitalization. The safety of therapy is assessed by the side effects that appear and appear-more-often in IVIG therapy rather than PE.